PEWARISAN KARAKTER YANG TERKAIT DENGAN KETAHANAN TERHADAP KEKERINGAN PADA KACANG TUNGGAK - M. Chozin; J.O Gardner; C.E Watson (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2006)
The genetic of traits related to drought-resistance in cowpea was studied using generation mean analysis. The two contrasting drought-resistance genotypes were crossed to generate F1, F2, F3, BC1, BC2, BC1S1, and BC2S1populations which were imposed to a controlled water deficit conditions from flowering to early pod formation. The analyses were performed on stem diameter, delayed leaf senescence, and leaf temperature which were identified in earlier study as good discriminators in discerning genotypes for drought-resistance. The resistant genotype was characterized by higher delayed leaf senescence, larger stem diameter, and lower leaf temperature . The means indicated that delayed leaf senescence was controlled by partial dominant gene(s) dan segregated toward resistance. Heterotic effect toward susceptibility was found on stem diameter but recombination and segregation had seemed to bring about a reversed direction. Partial dominant gene(s) also played an important role in governing leaf temperature toward susceptibility. The Hayman’s generation mean analysis suggested that additive effect was important in controlling the three traits. The dominant and epistatic (additive-additive and additive dominant) effects were significant on stem diameter, whereas additive-dominant effect was the only additional effect for leaf temperature, beside the additive effect.